Implementasi Perlindungan Hukum bagi Penyandang Disabilitas dalam Pembuatan Akta Autentik di Hadapan Notaris - Prasetyo, Teguh; Adjie, Thomas Wibisono Prasetya (Program Studi Kenotariatan Fakultas Hukum Universitas Pelita Harapan, 2024)
This study examines the implementation of legal protection for persons with disabilities in the process of executing authentic deeds before a notary with a particular focus on the alignment between actual practice and the provisions stipulated in Law No. 2 of 2014 concerning the Position of Notary and Law No. 8 of 2016 on Persons with Disabilities. Employing a normative and empirical juridical approach, this research combines legal literature analysis with field data gathered through interviews involving notaries, persons with disabilities, and disability advocacy organizations. The findings reveal several structural and practical barriers that hinder the full realization of legal rights for persons with disabilities in notarial services. These include the limited availability of sign language interpreters, the absence of Braille-format legal documents, the lack of physical accessibility in notary offices, and low awareness among notaries regarding inclusive service principles. Consequently, persons with disabilities are vulnerable to indirect legal discrimination and often do not receive equal legal protection. This study recommends strengthening technical regulations, providing disability-friendly infrastructure in notary offices, and offering specialized training on inclusive services for notaries. In doing so, the notarial service system can be transformed into one that ensures equality of rights and effectively accommodates the needs of all citizens, in accordance with the principles of social justice and human rights. Bahasa Indonesia Abstract: Penelitian ini membahas implementasi perlindungan hukum bagi penyandang disabilitas dalam proses pembuatan akta autentik di hadapan notaris dengan menitikberatkan pada kesesuaian praktik di lapangan terhadap ketentuan dalam Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris serta Undang-Undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas. Penelitian ini menggunakan pendekatan yuridis empiris yang mengombinasikan studi literatur hukum dengan hasil wawancara terhadap notaris, penyandang disabilitas, dan lembaga pendamping disabilitas. Temuan penelitian menunjukkan bahwa terdapat berbagai hambatan struktural dan praktis yang menghambat pemenuhan hak penyandang disabilitas dalam layanan kenotariatan. Hambatan tersebut antara lain mencakup minimnya ketersediaan Juru Bahasa Isyarat (JBI), absennya dokumen Braille untuk tunanetra, kurangnya sarana fisik yang aksesibel di kantor notaris, serta rendahnya kesadaran dan pemahaman notaris terkait prinsip inklusivitas. Akibatnya, penyandang disabilitas rentan mengalami diskriminasi hukum secara tidak langsung dan tidak memperoleh perlindungan hukum yang setara. Penelitian ini merekomendasikan adanya penguatan regulasi teknis, penyediaan fasilitas ramah disabilitas di kantor notaris, serta pelatihan khusus mengenai pelayanan inklusif bagi para notaris. Dengan demikian, diharapkan tercipta sistem layanan kenotariatan yang menjamin kesetaraan hak dan mampu mengakomodasi kebutuhan seluruh warga negara tanpa terkecuali, sesuai dengan prinsip keadilan sosial dan hak asasi manusia.